“diseño de un sistema de gestión de seguridad y salud ocupacional basado en las normas ohsas 18001:2007 y ley 29783, para disminuir el número de accidentes en la empresa metal mecánica siban srl- cajamarca” - Aguilar Ramos, Luis Alberto (2016)
The enterprise “SIBAN SRL” does not have an Assessment System of Risks which permits protect the workers from dangerous against their health, that is why me suggest to install an Occupational Health and Safety Assessment System with the purpose of diminish or eliminate risks, avoiding in this way economical loss, by accidents or by sanctions imposes for the Ministry of the Work. For that reason we made an analyze and diagnostic of the actual situation in the enterprise related with the safety and occupational health in order to identify the main risks which the works are exposed; and beginning for this, we propose correcting and preventing measure, with the existing legal framework established in Law No. 29783, Law of Health and Safety at Work Regulations and the DS. N ° 005-2012-TR approved on April 24, 2012, Supreme Decree No. 055-2010-EM, Regulation of Occupational Safety and Health in Mining, among others. Us a result of the actual situation analyze, we found that the enterprise fulfills with the 45 % of requirements demanded by the Safety and Health Regulations of Work. That percent set the enterprise in a deficient situation and the main of risks analyzed, are high and moderated. The Occupational Health and Safety Assessment System will be a help in order to better the workers well-being and hence of the enterprise profit.